Exploring the Relationship Between Parenting Styles and Callous-Unemotional Traits in Early Adolescents - Prasetiani, Artika Adi; Mahanani, Fatma Kusuma (Nusantara Journal of Behavioral and Social Science, 2024)
This study aims to evaluate the tendency of Callous-Unemotional (CU) traits in early adolescents based on their perceptions of parental parenting styles, specifically authoritarian, democratic, and permissive. The study employs a comparative method with a cross-sectional design. The sample comprises 236 middle school students in Pati Regency, selected using cluster random sampling. Data were collected using two scales: the Callous Unemotional Traits scale and the Parental Authority Questionnaire (PAQ), both of which have been validated for reliability. The results indicate significant differences in CU traits among adolescents based on the type of parenting style (p less than 0.05). Adolescents with authoritarian parenting tend to exhibit higher CU traits compared to those with democratic and permissive parenting styles. Democratic parenting generally results in lower CU traits, while permissive parenting shows varied outcomes. These findings support Baumrind's theory, which suggests that authoritarian parenting, characterized by strict control and lack of freedom, can hinder children's emotional and social development. The practical implications of this study highlight the importance of developing effective parenting strategies by parents and educators to reduce the tendency of CU traits in adolescents. Future research is recommended to involve larger and more diverse samples and to utilize a longitudinal design to better understand the development of CU traits over time. Abstrak: Penelitian ini bertujuan untuk mengevaluasi kecenderungan sifat Callous-Unemotional (CU) pada remaja awal berdasarkan persepsi mereka terhadap pola asuh orang tua, yaitu otoriter, demokratis, dan permisif. Penelitian ini menggunakan metode komparatif dengan desain cross-sectional. Sampel terdiri dari 236 siswa SMP di Kabupaten Pati yang dipilih menggunakan teknik cluster random sampling. Data dikumpulkan menggunakan dua skala: Skala Callous Unemotional Traits dan Parental Authority Questionnaire (PAQ), yang telah diuji validitas dan reliabilitasnya. Hasil penelitian menunjukkan bahwa terdapat perbedaan signifikan dalam kecenderungan CU Traits pada remaja berdasarkan tipe pola asuh orang tua (p kurang dari 0,05). Remaja dengan pola asuh otoriter menunjukkan kecenderungan CU Traits yang lebih tinggi dibandingkan dengan remaja yang mendapatkan pola asuh demokratis dan permisif. Pola asuh demokratis cenderung menghasilkan remaja dengan CU Traits yang lebih rendah, sementara pola asuh permisif menunjukkan hasil yang bervariasi. Temuan ini mendukung teori Baumrind yang menyatakan bahwa pola asuh otoriter yang ditandai dengan kontrol yang ketat dan kurangnya kebebasan dapat menghambat perkembangan emosional dan sosial anak. Implikasi praktis dari penelitian ini adalah pentingnya pengembangan strategi pengasuhan yang efektif oleh orang tua dan pendidik untuk mengurangi kecenderungan CU Traits pada remaja. Penelitian selanjutnya direkomendasikan untuk melibatkan sampel yang lebih besar dan lebih beragam serta menggunakan desain longitudinal untuk memahami perkembangan CU Traits dari waktu ke waktu.